Are personality disturbances in anorexia nervosa related to emotion processing or eating disorder symptomatology?. Issue 1 (December 2015) - Phillipou, Andrea; Gurvich, Caroline; Castle, David; Rossell, Susan
Abstract Background Anorexia Nervosa (AN) is a psychiatric illness associated with a number of personality disturbances. However, whether these personality characteristics are related to eating disorder symptomatology or emotion regulation is unclear. The aim of this study was to investigate these relationships. Results Twenty-four individuals with AN and 25 age- and premorbid intelligence-matched controls completed the Personality Diagnostic Questionnaire, and scores were correlated with measures of emotionality and negative mood states, and eating disorder symptomatology. AN was associated with increased scores on schizoid, borderline, avoidant, dependent, obsessive compulsive, negativistic and depressive personality dimensions, relative to controls. In AN, eating disorder symptomatology did not significantly correlate with scores on any personality dimension. However, a number of personality characteristics were found to correlate with negative mood states. Conclusions The findings suggest that personality disturbances in AN are not related to disorder-specific symptoms, but are related to negative mood states.